Discourse Style of Nigerian Coup Plotters - Anyachonkeya, Ngozi; Nwosu-Okoli, Ifeoma (European Scientific Journal, ESJ, 2023)
This paper focuses on investigating selected speeches of Nigerian coup plotters, with a view to ascertaining their discourse styles. The paper speculates that the broadcast idiolect revolves around propaganda, polemics, and discursive styles, including the fox, Tartuffe or tortoise style, where they intimidate their opponents and the civilian populace into submission. This paper, by its nature, involves both qualitative and quantitative kind of research as it relies heavily on observation and library research. The military class succeeded in intervention mission but failed abysmally in the thrust of salvation. Their selfish quest made them neocolonialists in military garb. This paper, therefore, argues that their dismal failure in political governance of their Motherland ends up leaving the masses much poorer and more disillusioned than they had been under the corrupt civilian government. The unmitigated disaster the military precipitated in political governance constrained Nigerian literary patriots to publish social satires – in all genres - amidst propaganda. This implies that they reprehensively indict the military villains and continuously call for a revolution from the disconsolate Nigerians.